Diet in pediatric inflammatory bowel disease: What to eat and what to avoid? - Ivan D. Milovanovich (Elsevier, 2024)
Pediatric inflammatory bowel diseases (PIBD) are autoinflammatory, multifactorial diseases that can affect children at any age. There are three types of PIBD: Crohn's disease, ulcerative colitis and unclassified colitis Both genetic and environmental factors are involved in the onset of PIBD. It is suspected that diet composition significantly contributes to IBD risk. On the other hand, in clinical presentation, malnutrition and growth retardation are one of the key signs and they are caused by anorexia and increased metabolism rate. We can say that diet is an important hallmark of PIBD in pathogenesis as well as in the therapy. Exclusive enteral nutrition (EEN) is the most widely used dietary intervention for the treatment of Crohn's disease, but is affected by a low tolerability, especially in pediatric patients. Promising alternative regimens are represented by Crohn's Disease Exclusion Diet (CDED), and other elimination diets, whose use is gradually spreading. The aim of the review is to provide an overview on the latest evidence about the role of nutrition and diet in pediatric IBD.